THE INFLUENCE OF THE FIRST LANGUAGE ON ENGLISH PRONUNCIATION AMONG UZBEK LEARNERS (Ustozlar uchun, 2026)
This study researches the influence of the Uzbek language which is first language on English pronunciation among Uzbek learners. The research provide with giving common pronunciation errors and analyzing of why it happens. A qualitative approach was used in this research and gets into observation and analysis of 9–11 grade students from a secondary school in the Fergana region in Uzbekistan. The findings reveal that learners occur difficulties in pronouncing certain English sounds, particularly /θ/ and /ð/, as well as separating of long and short vowels. Additionally, the problem which related to stress and intonation were observed. These difficulties are mainly caused by differences between the Uzbek and English phonological systems and limited communicative practice. The study shows the importance of pronunciation teaching and increased speaking activities to reduce L1 interference and improve learners’ pronunciation skills.